PENINGKATAN KESADARAN DALAM UPAYA PENCEGAHAN KOMPLIKASI DIABETES MELITUS PADA LANSIA - Trisna Vitaliati; Nurul Maurida; Irwina Angelia Silvanasi (LPPM Universitas dr. Soebandi, 2023)
The prevalence of diabetes mellitus (DIABETES MELLITUS) has increased both in the world and in Indonesia and is a cause of death in developed countries and has become an epidemic in developing countries. Diabetes mellitus with chronic hyperglycemia can cause abnormalities and failure in various organs of the body, especially nerves, heart, kidneys, eyes and blood vessels. The program to control non-communicable diseases has been carried out by the Public health center through programs in integrated coaching post, but health promotion regarding non-communicable diseases is also needed at the integrated service post. Community service activities aim to increase the knowledge of the elderly with diabetes mellitus in prevention efforts and form a positive attitude about DIABETES MELLITUS. Activities carried out in the form of health education and leaflet distribution, early screening and monitoring of self-care activities carried out. The results of this community service activity showed that there was an increase in the knowledge of the elderly about non-communicable diseases, especially diabetes mellitus and there was an increase in public awareness about promotive and preventive efforts from the disease. Continuous community service activities for the elderly and the community in general are important to do so that they can improve the health status of the community.